2017
DOI: 10.3390/app7020149
|View full text |Cite
|
Sign up to set email alerts
|

CFD Studies of the Effects of Waveform on Swimming Performance of Carangiform Fish

Abstract: Carangiform fish, like mackerel, saithe and bass, swim forward by rhythmically passing body waves from the head to the tail. In this paper, the undulating motions are decomposed into the travelling part and the standing part by complex orthogonal decomposition (COD), and the ratio between these two parts, i.e., the travelling index, is proposed to analyse the waveform of fish-like movements. To further study the relative influences of the waveform on swimming performance, a self-propelled model of carangiform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The structures of the vortex street are double-row, and there are no obvious changes in Figure 10. This result is consistent with the conclusion in our previous study (Cui, Gu, Li, & Jiang, 2017), in which we found that the wave number of body motions has little effect on swimming performance.…”
Section: Vortex Analysissupporting
confidence: 94%
“…The structures of the vortex street are double-row, and there are no obvious changes in Figure 10. This result is consistent with the conclusion in our previous study (Cui, Gu, Li, & Jiang, 2017), in which we found that the wave number of body motions has little effect on swimming performance.…”
Section: Vortex Analysissupporting
confidence: 94%
“…This makes it challenging to directly link our model of locomotion behaviour with biomechanical (e.g. Bandyopadhyay, 2002; Cui et al., 2017; Lighthill, 1971) or behavioural models (e.g. Oteiza et al., 2017) that describe movement of the migrant's body.…”
Section: Discussionmentioning
confidence: 99%
“…Note that in anguilliform studies it is common to use the product of f and a peak-to-peak undulation amplitude, A, as the characteristic velocity in the Reynolds number calculation. However, since undulation amplitude is an output of the model and cannot be known a priori, I elected to use a characteristic velocity seen in fish literature as an input velocity scale, f L [45,46]. Illustrations of the peak-to-peak amplitude, A are given in Figures 1 and 2.…”
Section: Methodsmentioning
confidence: 99%
“…Since it was desired to have a fluid scaling parameter as an input to the model, an input Reynolds number was defined in Eq. 2, based on a characteristic length that was the swimmer's body (L) and a frequency based characteristic velocity that was the product of the undulation frequency and the swimmer's body length, f L [45,46]. Many anguilliform swimming studies use the characteristic velocity as f A, where A is the peakto-peak undulation amplitude.…”
Section: Symmetry Within Each Half-stroke Cyclementioning
confidence: 99%